Удмуртская кухня: справочное издание / Г. И. Соковнин - Соковнин Герман Иванович (Удмуртия, 2012)
Экземпляры: КО (20141121) / Инвентарный номер: 51216 / Цена: 300. 00. / Сис.шифр: 36.99(2Рос. Удм) / Авт.знак: С 59 / ГРНТИ: 65 / ББК: 36.99(2Рос. Удм)